Solubility determination and thermodynamic modelling for 2-amino-4-chlorobenzoic acid in eleven organic solvents from T = (278.15 to 313.15) K and mixing properties of solutions. (March 2017) - Li, Xinbao; Wang, Mingju; Cong, Yang; Du, Cunbin; Zhao, Hongkun
Graphical abstract: Highlights: Solubility of 2-amino-4-chlorobenzoic acid in eleven solvents were determined. Four thermodynamic models were employed to correlate the solubility data. The mixing properties of solutions were calculated. Abstract: The solubility of 2-amino-4-chlorobenzoic acid in eleven organic solvents including N -methyl-2-pyrrolidone, ethanol, n -propanol, isopropanol, ethyl benzene, toluene, n -butanol, acetonitrile, ethyl acetate, 1, 4-dioxane and acetone were determined experimentally using the isothermal saturation method over a temperature range from (278.15 to 313.15) K under 101.2 kPa. Within the temperature range studied, the mole fraction solubility of 2-amino-4-chlorobenzoic acid in the solvents increased with a rise of temperature. On the whole, they obeyed the following order from high to low in the selected solvents: N- methyl-2-pyrrolidone > acetone > 1, 4-dioxane > ethyl acetate > ethanol > isopropanol >  n -propanol >  n -butanol > acetonitrile > toluene > ethyl benzene. The solubility values obtained for 2-amino-4-chlorobenzoic acid were correlated with the modified Apelblat equation, λh equation, Wilson model and NRTL model. The largest values of root-mean-square deviation ( RMSD ) and relative average deviation ( RAD ) were 8.25 × 10 −4 and 3.35%, respectively. The modified Apelblat equation correlated the experimental solubility best on the basis of the result of AIC analysis. Furthermore, the mixing Gibbs energy, mixing enthalpy, mixing entropy, activity coefficient ( γ 1 ∞ ) and reduced excess enthalpy ( H 1 E, ∞ ) at infinitesimal concentration were determined. Solubility and thermodynamic studies are very important for optimizing the purification process of 2-amino-4-chlorobenzoic acid.